Emerging Issues in International Human Rights Law - Reddy, Edula Jyothi (International Journal of Law, Human Rights and Constitutional Studies; Vol 5 No 1 (2023): International Journal of Law, Human Rights and Constitutional Studies, 2023)
This review delves into the multifaceted landscape of international human rights law, shedding light on the emergent issues that challenge its principles and application in today's world. Four key thematic areas are explored in-depth: Technology and Human Rights, Climate Change and Human Rights, Migration and Human Rights, and Economic Disparities and Human Rights. In the realm of Technology and Human Rights, the rapid rise of digital technologies, surveillance, and artificial intelligence pose new ethical and legal dilemmas. The balance between security and privacy, the attribution of cyberattacks, and the responsible development of AI demand international attention and consensus. Climate Change and Human Rights illuminate the devastating impacts of environmental crises on vulnerable communities. Displacement due to climate-related factors, threats to environmental rights, and corporate responsibility in the face of climate change are pressing issues that require comprehensive international solutions. Migration and Human Rights grapple with the complex challenges of border control, detention, and the protection of asylum seekers and refugees. The principle of non-refoulement and the fight against human trafficking and smuggling underscore the urgency of robust international frameworks. Economic Disparities and Human Rights delve into poverty, income inequality, and unequal access to education and healthcare. Recognizing the multidimensional nature of poverty and addressing systemic barriers are central to the pursuit of economic and social rights. As international human rights law adapts to these emergent issues, it stands as a critical tool for addressing contemporary global challenges while striving to uphold the dignity and rights of all individuals.